2016
DOI: 10.1002/jaba.358
|View full text |Cite
|
Sign up to set email alerts
|

Further refinement of video‐based brief multiple‐stimulus without replacement preference assessments

Abstract: We compared the results of a brief video-based multiple-stimulus without replacement preference assessment with no access to chosen activities (MSWO-NO) to the results of the same assessment with access (MSWO-WA) with four children with autism. We also compared instructor rankings of activities to MSWO-WA results. Strong to moderate correlations between MSWO-NO and MSWO-WA assessment results were found across all participants. The correlation between MSWO-WA and instructor rankings ranged from strong to low ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…For example, Clark et al presented items via video to children with ASD in a paired-stimulus video format without providing access contingent on selection and found that even if the individual did not physically have access to the item, highly preferred stimuli did function as reinforcers (50). Brodhead et al (38) extended the work of Clark et al and found similar results when assessing preference for activities. Finally, Brodhead and Rispoli demonstrated that video assessments may also be used to accurately assess preference for novel stimuli (51).…”
Section: Potential Benefits Of Implementing Video-based Stimulus Prefmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, Clark et al presented items via video to children with ASD in a paired-stimulus video format without providing access contingent on selection and found that even if the individual did not physically have access to the item, highly preferred stimuli did function as reinforcers (50). Brodhead et al (38) extended the work of Clark et al and found similar results when assessing preference for activities. Finally, Brodhead and Rispoli demonstrated that video assessments may also be used to accurately assess preference for novel stimuli (51).…”
Section: Potential Benefits Of Implementing Video-based Stimulus Prefmentioning
confidence: 65%
“…In recent literature, preference assessments are most often used to identify individualized reinforcing stimuli to offer as a reinforcer during a behavioral intervention. These assessments are methodologically rigorous and have been shown to be more reliable and effective at assessing preference and identifying reinforcers (37) than the sole reliance on parent and caregiver suggestions (38, 39), making them a potentially valuable asset to the field of AAI.…”
Section: Overview Of Stimulus Preference Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark et al found the video‐based preference assessment with no access accurately identified toys that functioned as reinforcers for three of four participants. In a similar study, Brodhead, Abston, Mates, and Abel () compared the results of a video‐based brief MSWO without access, to the same preference assessment format when access was provided. Brodhead et al found that the video‐based preference assessment when contingent access was not provided had moderate to strong positive correlations to the same assessment when access was provided.…”
mentioning
confidence: 99%
“…That is, exposure to stimuli did not appear to affect obtained preference for the participants. However, one limitation of Brodhead et al () and Brodhead and Rispoli is that researchers did not conduct a reinforcer assessment to validate outcomes obtained during the video‐based preference assessments without access to selected stimuli.…”
mentioning
confidence: 99%